Devising of public health policies during Covid-19 pandemic in American countries - Landeros Olvera, Erick (Universidad de Sonora, 2020)
Introduction: The pandemic has generated an immediate response in the form of global actions that have not either been tested or evaluated, since there has been little time to check the results. It is essential to prepare public policies to implement the regulations for such actions within health programs. Objective: Present a proposal for the implementation of health policies aimed at solving problems resulting from the Covid-19 pandemic. Development: As a result of the epidemics recorded in history, health policies have developed programs that offered prevention and treatment solutions. Currently, the emergency situation has forced us to work to remedy, understand, and improve such health policies in the American countries. The World Health Organization has made efforts to help delimit the pandemic through the different governments of the Americas, but how can feasible policies be prepared if the situation in each country has shown different health contingency strategies? The proposal for the devising and execution of public health policies is as follows: 1. Define the problem, 2. Generate solutions, 3. Main objective, 4. Write strategies, 5. Implementation, 6. Planning, 7. Execution, 8. Results, 9. Evaluation, 10. Feedback. Conclusions: Public health policies had to be adapted to the financial and cultural reality of each country, considering current health challenges; nevertheless, health professionals, when proposing public policies, must be aware of seeking support from Congress, so this could be the voice to represent the proposal of those who are on the scene.